Pathophysiology and Management of Refractory Rheumatoid Arthritis: A Narrative Literature Review - Ardanny, Ali; Najirman (HM Publisher, 2024)
Refractory rheumatoid arthritis is rheumatoid arthritis that fails to achieve low levels of disease activity using 2-3 DMARDS treatment and at least one other first-line bDMARD. The definition of refractory action is based on the number of failed DMARDs, the scale of the problem, and risk factors for a refractory disease course. Until now, there has been no further research discussing the pathophysiology of refractory RA, but it is known that TNF-α, IL-6, and IL-1 are the most important mediators that enable cell migration and inflammation in RA. IL-6 in particular, acts directly on neutrophils, which then contribute to inflammation and joint destruction by secreting proteolytic enzymes. The main goal to be achieved in RA is remission, low disease activity and an alternative goal for those who fail to achieve therapy targets. Currently, there are several bDMARD agents that can be used as therapy for refractory RA, namely TNF alfa inhibitors, B cell depletion agents, T cell activity inhibitors, and cytokine inhibitors.